The greatest treasure hunt in history : the story of the Monuments Men - Edsel, Robert M. (Scholastic Focus, 2021)
Examines the true story of the Monuments Men, a group of eleven men and one woman, not soldiers but museum curators, architects, archivists, art scholars, educators, and artists, from America and Britain who volunteered to go into Europe at the height of World War II and locate and save priceless treasures and works of art in danger from the Nazis.